A Critical Analysis of Accomplice Evidence in Criminal Trial: Dr.Anand Prakash - Juhi Naseem (International journal of economic perspectives, 2022)
The present paper explains the admissibility and reliability of accomplice as a witness. Accomplice, though not defined anywhere in the Indian Evidence Act; finds its place as a competent witness under the Act.This paper is about how an accomplice’s testimony is credible and it differs from a government approver and a co accused, mentioned under Section 30 of the Indian Evidence Act,1872.